Microstructure observations on butt joint composed of Nb3Sn CIC conductors. (January 2017) - Obana, Tetsuhiro; Tokitani, Masayuki; Takahata, Kazuya; Kizu, Kaname; Murakami, Haruyuki
Highlights: Microstructure observations on the butt joint composed of Nb3 Sn CIC conductors were conducted using an FE-SEM. Nb3 Sn strands and a copper sheet were butted properly at the interface of the butt joint. There were hairline cracks in the Nb3 Sn layers of the strands near the joint interface. Abstract: To precisely evaluate a butt joint technology for the JT-60SA CS coils, microstructure observations on the butt joint composed of Nb3 Sn CIC conductors were conducted using a FE-SEM. As a sample for the observations, the butt joint sample utilized in the joint resistance measurement was used. During the sample fabrication, the butt joint sample was heated up to about 920 K from room temperature for diffusion bonding after heat treatment for Nb3 Sn production. Then, the sample was subjected to the cycles of electromagnetic force in the joint measurement. The observation results indicated that Nb3 Sn strands and a copper sheet were butted properly at the interface of the butt joint. In addition, there were hairline cracks in the Nb3 Sn layers of the strands near the interface. To investigate a cause of the crack initiation, the stresses generated in the butt joint under same conditions were analyzed using a simple model. As a result, the cracks would occur with an axial compressive stress generated by the butt joint fabrication.